The Effect of Social Media on Student Learning Achievement at SD Negeri Daya 1 Makassar - Nurhidayah Nurhidayah; Wahyulla Alannasir; Riskal Fitri (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to describe the description of the learning achievement of students at SD Negeri Daya 1 Makassar, to explain how much influence social media has on the learning achievement of students at SD Negeri Daya 1 Makassar and to find out the factors that influence student achievement at SD Negeri Makassar Power 1. The type of research used in this study used total sampling so that as many as 27 students were obtained from the total number of students. The instrument used is in the form of a social media questionnaire and to find out the learning achievement of students is in the form of end-of-semester scores. Based on the results of the research, the hypothesis test found that there was a significant influence of social media on the learning achievement of SD Negeri Daya 1 Makassar students. This can be seen from the t-value of social media, namely -2.154 > 1.708 and a significant level of 0.041 <0.05.